Simultaneous 6300 Å airglow and radar observations of ionospheric irregularities and dynamics at the geomagnetic equator - Hickey, Dustin A. (2018)
In March 2014 an all-sky imager (ASI) was installed at the Jicamarca Radio Observatory (11.95°S, 76.87°W; 0.3°S MLAT). We present results of equatorial spread F (ESF) characteristics observed at Jicamarca and at low latitudes. Optical 6300 and 7774Å airglow observations from the Jicamarca ASI are compared with other collocated instruments and with ASIs at El Leoncito, Argentina (31.8°S, 69.3°W; 19.8°S MLAT), and Villa de Leyva, Colombia (5.6°N, 73.52°W; 16.4°N MLAT). We use Jicamarca radar data, in incoherent and coherent modes, to obtain plasma parameters and detect echoes from irregularities. We find that ESF depletions tend to appear in groups with a group-to-group separation around 400–500km and within-group separation around 50–100km. We combine data from the three ASIs to investigate the conditions at Jicamarca that could lead to the development of high-altitude, or topside, plumes. We compare zonal winds, obtained from a Fabry–Pérot interferometer, with plasma drifts inferred from the zonal motion of plasma depletions. In addition to the ESF studies we also investigate the midnight temperature maximum and its effects at higher latitudes, visible as a brightness wave at El Leoncito. The ASI at Jicamarca along with collocated and low-latitude instruments provide a clear two-dimensional view of spatial and temporal evolution of ionospheric phenomena at equatorial and low latitudes that helps to explain the dynamics and evolution of equatorial ionospheric/thermospheric processes.